Therapeutic antisense oligonucleotides against cancer: hurdling to the clinic - Moreno, Pedro M. D.; Pêgo, Ana P. (Frontiers in Chemistry, 2014)
Under clinical development since the early 90’s and with two successfully approved drugs (Fomivirsen and Mipomersen), oligonucleotide-based therapeutics have not yet delivered a clinical drug to the market in the cancer field. Whilst many pre-clinical data has been generated, a lack of understanding still exists on how to efficiently tackle all the different challenges presented for cancer targeting in a clinical setting. Namely, effective drug vectorization, careful choice of target gene or synergistic multi-gene targeting are surely decisive, while caution must be exerted to avoid potential toxic, often misleading off-target-effects. Here a brief overview will be given on the nucleic acid chemistry advances that established oligonucleotide technologies as a promising therapeutic alternative and ongoing cancer related clinical trials. Special attention will be given towards a perspective on the hurdles encountered specifically in the cancer field by this class of therapeutic oligonucleotides and a view on possible avenues for success is presented, with particular focus on the contribution from nanotechnology to the field.